High frequency ultrasound can detect improvement of lesions in juvenile localized scleroderma. Issue 5 (September 2014) - Porta, Francesco; Kaloudi, Olga; Garzitto, Alice; Prignano, Francesca; Nacci, Francesca; Falcini, Fernanda; Matucci Cerinic, Marco
Abstract Background. Juvenile Localized Scleroderma (JLS) causes functional disabilities and cosmetic deformities. Evaluation and follow-up of lesions are mandatory to understand the disease evolution. The objective of this study is to evaluate the usefulness of skin ultrasonography (US) in monitoring the response to treatment in JLS. Methods. Ten patients (age: 101, 7 ± 66, 2 months; 7 M, 3 F) affected by juvenile onset LS underwent sequential US exams (at baseline and after 6 months). Skin thickness was measured by using high-frequency US (18 MHz). All patients were evaluated both clinically (modified Rodnan Skin Score, mRSS) and by US (dermal thickness) at baseline and at 6 months. At baseline, 6/10 patients received 3 pulses of corticosteroids (solumedrol 30 mg/kg/day for 3 consecutive days, then oral steroids (1mg/kg), and methotrexate s.c. (15 mg/mq/week). After 6 months, 1/6 was switched to mycophenolate mofetil (25 mg/kg/day) due to inefficacy of MTX; 4/10 did not receive any further therapy. Results. US showed a thicker dermis and a thinned hypodermis in the lesional skin areas in respect to the healthy ones (p < 0.05). After treatment, in seven patients a clinical improvement (decrease of mRSS) was found. In six of these patients, US showed a decrease of dermal thickness showing a correlation with clinical data. Three patients who did not receive drugs showed unmodified images and clinical findings. Conclusion. US can help the assessment of skin and hypodermis in JLS and can detect an improvement of the lesions.